Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more
Download
Standard view
Full view
of .
Save to My Library
Look up keyword
Like this
207Activity
0 of .
Results for:
No results containing your search query
P. 1
ejercicios resueltos mate algebra lineal

ejercicios resueltos mate algebra lineal

Ratings:

4.67

(6)
|Views: 54,484|Likes:
Published by apolo456

More info:

Published by: apolo456 on Jul 11, 2008
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

01/29/2014

pdf

text

original

 
1)
Solución2)3)
 
 
UNIDAD VIEJERCICIO 1DETERMINE SI LATRANSFORMACIÓN DADA DE V W ES LINEAL O NO.
I.- T: R
2
R
3
; T (X, Y)= (X, Y)T [ (X
1,
Y
1
) + (X
2
, Y
2
) ] = T [(X
1,
+X
2
) + (Y
1
, Y
2
)]= [(Y
1,
+Y
2
) + (X
1
, X
2
)](Y
1,
+Y
2
) = T(X
1
, Y
1
) Y (X
1
, X
2
) = T(X
2
, Y
2
)T [ (X
1,
Y
1
) + (X
2
, Y
2
) ] = T(X
1
, X
2
) + T (Y
1
, Y
2
)T [ K (X, Y) ] = T ( KX, KY) = KT(X, Y) = (Y, X)
SI ES UNA TRANSFORMACIÓN LINEAL
EJERCICIO 22.- T: R
3
R
2
; T (X, Y, Z) = (1, Z)T [ (X
1,
Y
1 ,
Z
1
) + (X
2
, Y
2 ,
Z
2
) ] = T [(X
1,
+X
2
) + (Y
1
+ Y
2
) (Z
1
+ Z
2
)]
 
 = [( 1 ) + (Z
1
, Z
2
)]T [ (1, Z
1
) + (1, Z
2
)] = T(1, Z
1
) + T(1, Z
2
)T [ K (X, Y, Z) ] = T ( KX, KY, KZ) = KT(X, Y, Z) = K(1, Z) = (K, KZ)
NO ES UNA TRANSFORMACIÓN LINEAL.
EJERCICIO 32.- T: R
3
R
2
; T (X, Y, Z) = (X, Y)T [ (X
1,
Y
1 ,
Z
1
) + (X
2
, Y
2 ,
Z
2
) ] = T [(X
1,
+X
2
) + (Y
1
+ Y
2
) (Z
1
+ Z
2
)]= [( X
1
, X
2
) + (Y
1
, Y
2
)]T [ (X
1
, Y
1
) + (X
1
, Y
2
)] = T(X
1
, Y
1
) + T(X
2
, Y
2
)T [ K (X, Y, Z) ] = T ( KX, KY, KZ) = K(X, Y) = KT(X, Y)
SI ES UNA TRANSFORMACIÓN LINEAL.
EJERCICIO 44.- T: R
2
R
2
; T (X, Y) = (1, Y)T [ (X
1,
Y
1
) + (X
2
, Y
2
) ] = T [(X
1,
+X
2
) + (Y
1
+ Y
2
)]= [( 1 ) + (Y
1
, Y
2
)]T [ (1, Y
1
) + (1, Y
2
)] = T(1, Y
1
) + T(1, Y
2
)T [ K (X, Y) ] = T ( KX, KY,) = KT(X, Y) = K(1, Y) = (K, KY) 
NO ES UNA TRANSFORMACIÓN LINEAL
EJERCICIO 55.- T: R
2
R
2
; T (X, Y) = (X + Y, X - Y, 3Y)T [ (X
1,
Y
1
) + (X
2
, Y
2
) ] = T [(X
1,
+X
2
) + (Y
1
+ Y
2
)]

You're Reading a Free Preview

Download
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->